2017
DOI: 10.1002/ijch.201700023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Octaketides from the Cytosporone Family

Abstract: Cytosporone B and its simple analogues (e. g., amoitone B) were recently identified as unique agonists for nuclear orphan receptor Nur77. In this study, we have developed an aldehyde C‐H activation method for preparing natural and designer analogues from the cytosporone family. In addition, a comprehensive investigation of the compounds’ biological activities and pharmacological liabilities has been conducted and new structure activity relationships (SAR) were derived from the data. Most notably, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Recently, novel, structurally similar octaketides have been isolated and a few approaches for the synthesis of these molecules were reported (Meza et al 2015, Cochrane et al 2016, Zamberlam et al 2012, Dos Santos et al 2009, Zhenga et al 2019, Dos Santos et al 2020. These findings also revealed that cytosporones are potentially pharmaceutical and agrochemical agents (Meza et al 2015, von Delius et al 2017. The most representative compounds in this class of resorcinolic lipids are cytosporones A-E (1-5, Figure 1), isolated from the endophytic fungi Cytospora sp.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, novel, structurally similar octaketides have been isolated and a few approaches for the synthesis of these molecules were reported (Meza et al 2015, Cochrane et al 2016, Zamberlam et al 2012, Dos Santos et al 2009, Zhenga et al 2019, Dos Santos et al 2020. These findings also revealed that cytosporones are potentially pharmaceutical and agrochemical agents (Meza et al 2015, von Delius et al 2017. The most representative compounds in this class of resorcinolic lipids are cytosporones A-E (1-5, Figure 1), isolated from the endophytic fungi Cytospora sp.…”
Section: Introductionmentioning
confidence: 86%
“…Interestingly, compound 14 that features a longer alkyl side chain with an alcohol functionality was not active against any of the tested cancer cell lines, similar to earlier findings about diminished cytotoxicity of cytosporone B (5) analogues with hydroxy-functionalized alkyl chains. 22 S16). Among the 14 tested cytosporones, trihydroxy-isochroman-3one cytosporone D (2) exhibited excellent activity against C. albicans ATCC 10261 (minimum inhibitory concentration [MIC] = 6.25−3.12 μg/mL; minimum fungicidal concentration [MFC] = 50 μg/mL) and all the tested Gram-positive bacteria (MICs ranging 1.56−12.5 μg/mL; minimum bactericidal concentrations [MBCs] 6.25−50 μg/mL), 19,20 including the antibiotics-resistant S. aureus MRSA strain ATCC 33592 (MIC = 6.25−3.12, MBC = 25 μg/mL).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We prepared eight biologically active octaketide natural products (i.e., dothiorelones, cytosporones, and phomopsin C). In a related study, we synthesized 12 analogs of the cytosporone family and ultimately found an increase in cytotoxicity with a densely fluorinated acyl carbogenic chain …”
Section: Aldehyde C–h Bond Functionalizationmentioning
confidence: 99%